2012
DOI: 10.5194/hess-16-2801-2012
|View full text |Cite
|
Sign up to set email alerts
|

SWAT use of gridded observations for simulating runoff – a Vietnam river basin study

Abstract: Abstract. Many research studies that focus on basin hydrology have applied the SWAT model using station data to simulate runoff. But over regions lacking robust station data, there is a problem of applying the model to study the hydrological responses. For some countries and remote areas, the rainfall data availability might be a constraint due to many different reasons such as lacking of technology, war time and financial limitation that lead to difficulty in constructing the runoff data. To overcome such a l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 30 publications
7
42
0
Order By: Relevance
“…To further reduce residual cloud contamination, atmospheric, and bidirectional effects, we produced a monthly NDVI dataset using the maximum value composite (MVC) method to obtained monthly NDVI (Holben, 1986;Piao, 2003;Fang, 2004;Peng et al, 2011), which were averaged with the growing season NDVI for further analyses. The bilinear interpolation method was used to extract the NDVI values corresponding to the station data based on grid vegetation data with a spatial resolution of 0.083° (Vu et al, 2012). Finally, monthly NDVI sequence data, corresponding to select climate stations in China and spanning the period from 1982 to 2011, were generated.…”
Section: Ndvi Datamentioning
confidence: 99%
“…To further reduce residual cloud contamination, atmospheric, and bidirectional effects, we produced a monthly NDVI dataset using the maximum value composite (MVC) method to obtained monthly NDVI (Holben, 1986;Piao, 2003;Fang, 2004;Peng et al, 2011), which were averaged with the growing season NDVI for further analyses. The bilinear interpolation method was used to extract the NDVI values corresponding to the station data based on grid vegetation data with a spatial resolution of 0.083° (Vu et al, 2012). Finally, monthly NDVI sequence data, corresponding to select climate stations in China and spanning the period from 1982 to 2011, were generated.…”
Section: Ndvi Datamentioning
confidence: 99%
“…The following indicator criteria were applied to evaluate the grid-based data sets based on WSD: the linear correlation coefficient (CF), root mean square error (RMSE), mean absolute error (MAE), multiplicative bias (MBias) and Nash-Sutcliffe Coefficient (NSE) [32,45,47]. The mathematical expressions of these criteria are as follows:…”
Section: Accuracy Assessments Of the Grid-based Data Setsmentioning
confidence: 99%
“…Twenty sensitive parameters were selected according to previous studies [5,47,66,67] and tested in the SWAT-CUP to perform a sensitivity analysis. Fourteen sensitive parameters were selected according to their performances in the sensitivity analysis, and manual calibration and auto-calibration were performed using a Sequential Uncertainty Fitting (SUFI-2) algorithm to achieve acceptable performance [68][69][70][71][72][73].…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…Looking at the spatial distribution of seasonal precipitation and temperature ( Figures S1 and S3), one could see that there is no significant difference among different climate datasets, however the temporal variability (yearly precipitation) is noticeable ( Figure S2). Many studies have assessed the impacts of gridded data for simulating runoff [14,42,43]. The results showed that their quality vary significantly from one region to the other.…”
Section: Model Performance and Parametersmentioning
confidence: 99%
“…The results showed that their quality vary significantly from one region to the other. For example, Vu et al [42] showed poor performance of the PERSIANN (precipitation estimation from remotely sensed information using artificial neural networks) and TRMM (tropical rainfall measuring mission) rainfall data compared to the station data.…”
Section: Model Performance and Parametersmentioning
confidence: 99%